Exercise fidelity and progression in a supervised exercise programme for adults with venous leg ulcers. Issue 5 (6th June 2018) - Klonizakis, Markos; Gumber, Anil; McIntosh, Emma; King, Brenda; Middleton, Geoff; Michaels, Jonathan A; Tew, Garry A
Abstract : Despite exercise being included in the recommended advice for patients with venous leg ulcers, there is a fear shared by clinicians and patients that exercise may be either inappropriate or harmful and actually delay rather than promote healing. Therefore, before implementing a larger‐scale study exploring the effects of a supervised exercise programme in patients with venous ulcers being treated with compression therapy, it is important to assess exercise safety as well as fidelity and progression in a feasibility study. Eighteen participants randomised in the exercise group were asked to undertake 36 (3 times/week for 12 weeks) 60‐min exercise sessions, each comprising moderate‐intensity aerobic, resistance, and flexibility exercise components. For the purposes of this paper, we analysed the data collected during the exercise sessions. The overall session attendance rate was 79%, with 13 of 18 participants completing all sessions. No in‐session adverse events were reported; 100% aerobic components and 91% of resistance components were completed within the desired moderate‐intensity target. Similarly, 81% of aerobic components and 93% of flexibility components were completed within the prescribed duration targets. Our data showed that patients with venous ulcers could safely follow a supervised exercise programme incorporating moderate‐intensity aerobic, resistance, and flexibility components.